The Flogging of the Imams and the Forging of Islamic Constitutionalism - Kurniawan Arif Maspul; Hasbi Yusron; Aditia Nugraha (Indonesian Journal Publisher, 2026)
This study examines the foundational struggle between independent jurists and caliphal power during the Umayyad–Abbasid transition as a critical juncture in Islamic political thought. Through a qualitative historical-comparative analysis that process‑traces the principled resistance of Imams Abū Ḥanīfa and Mālik ibn Anas, it demonstrates how their refusal of state appointments, endurance of torture, and assertion of law above the ruler forged an enduring “separation of powers.” The analysis reveals that their stances institutionalised the ulama as autonomous guardians of Sharia, insulating legal pluralism—the four Sunni schools—from executive manipulation and creating a proto‑constitutional order centuries before Western analogues. The study further traces how this dynamic shaped legitimacy bargains, financial independence, and the soft power of transnational scholarly networks, yielding a normative architecture that constrained tyranny and preserved a vibrant legal tradition. Contemporary implications are drawn for judicial independence, academic freedom, and accountable governance in Muslim‑majority states, anchoring global rule‑of‑law principles in indigenous Islamic heritage.